Effect of growing conditions on growth, seed yield and quality attributes in cherry tomato (Solanum lycopersicum var cerasiferme) - VIDYADHAR, BONTHA; TOMAR, B S; SINGH, BALRAJ; KADDI, GIRISH (The Indian Journal of Agricultural Sciences, 2015)
A study was conducted at CPCT, IARI, New Delhi to investigate the effect of different growing conditions on plant growth, seed yield and quality traits in cherry tomato cv. Pusa Cherry Selection 1 grown under three different environmental conditions, viz. semi-climate controlled polyhouse (P1), naturally ventilated polyhouse (P2) and insect proof nethouse (P3). Among the structures P3 recorded significantly higher plant growth up to 60 days after transplanting (DAT) (217.68 cm) as compared to P2 and P1. However, at 120 DAT the plant growth was higher in P1 (313.68 cm), followed by P2 (280.40 cm) and P3 (265.59 cm). The days to 50% flowering was earlier in P3 (24.74 days) than P2 and P1. Significantly higher number of flowers per truss (115.16), number of berries per truss (39.15) number of mature berries (25.85) were noted in P1 as compared to P2 and P3. The berry weight (5.12 g), number of seeds per berry (34.52), 100 seed weight (0.113 g) and seed yield per berry (0.075 g) were recorded significantly higher values in P1 in comparison to P2 & P3. The seed quality parameters, viz. germination (84.63%), vigour index-I (532.53) and vigour index - II (1.29) were higher, whereas lower values for electrical conductivity (0.007 Î¼S/g/cm) was recorded in P1 than P2 & P3. The benefit cost ratio (BCR) is higher in P3 (1:2.70) followed by P1 (1:1.62) and lower in P2 (1:1.35).